Threaded magazine: Adopting a Culturally Connected Approach - Grieve, Fiona (2022)
It has been over ten years since the Practice Report, The site of Publication in Contemporary Practice (Grieve & Redmond, 2009) introduced the term Publication Platform to describe a series of distinctive editorial modes and publishing spaces. Central to this report was the inclusion of Threaded magazine and the role of collaboration to lead content and in doing so affect practice as a critical editorial and design strategy. This article presents the strategies on how Threaded adopted a holistic and culturally connected approach. The structure of the article examines how the publication encapsulates the three principles of Te Tiriti o Waitangi: Participation, Protection and Partnership, as a guiding underlying foundation. This editorial model instils the uniqueness of cultural connections within because it draws from who Threaded are as a collective, determined by the people we associate and collaborate with.  The Project 16/2 will be discussed, presenting a reflection on the process of self-discovery, employing the tradition of storytelling to convey the te ihi (essence) of who Threaded is. Edition 20 and 21 advance the learnings from 16/2 and this article examines the collaboration with cultural advisors, Kaumātua and Kuia to ensure the kaupapa of these issues adhere to tikanga Māori and Mātauranga Māori kawa (protocols).  To ensure what Threaded’s editors understand, and share is authentic and appropriate, advice and guidance is seek from our Kaumatua and Kuia (elders) walking within the realm of tradition as they are the carriers of the knowledge carefully passed down from our ancestors.